Strategic Military Tactics in Kautilya’s Arthashastra: An Analytical Study - Ghimire, Sanjay (Janajyoti Journal, 2024)
Strategic military tactics are the intentional and coordinated moves and strategies used by military forces to accomplish specific political or military goals. This work analyzes the sophisticated military doctrines in Kautilya’s Arthashastra, highlighting their strategic relevance in both historical and modern contexts. The article provides a comprehensive qualitative analysis of the strategic military tactics detailed in Kautilya’s Arthashastra, an essential text on ancient Indian statecraft and warfare. Utilizing a qualitative content analysis method, the study closely examines Kautilya’s military doctrines, focusing on strategic and tactical maneuvers designed to achieve political goals. It delves into Kautilya’s classifications of war, open and deceptive battle tactics, foreign policy measures, defense strategies, army organization, and battle formations. By exploring Kautilya’s perspectives on war and governance, the paper highlights the profound insights of Eastern philosophy in the areas of foreign policy and statecraft. It emphasizes the continuing relevance of Kautilya’s strategic military concepts in contemporary settings, showcasing the sophistication of Eastern thought on warfare, conflict, and national interests. The study concludes that Kautilya’s Arthashastra remains a timeless masterpiece of military strategy and statecraft, offering enduring lessons for modern policymakers and military strategists.